UNDERSTANDING THE RELATIONSHIP BETWEEN BIODIVERSITY AND CLIMATE CHANGE AND ITS OVERALL IMPACT ON THE FLORA AND FAUNA LIFE - Dr.Sumanta Bhattacharya; Bhavneet Kaur Sachdev (International Engineering Journal For Research & Development, 2021)
Excess use of ecosystem and natural resources have contributed to climate change which has not only affected the humans but also animals and plants . Over the years thousand of animals and birds have become extinct because of continue burning of fossil fuel , air pollution and water pollution which have killed many . Deforestation has made millions of animals and plants species homeless along with tribal community . The government have introduced many policies in India and have been part of many of the International convention to preserve wildlife and biodiversity . It is the biodiversity and afforestation which can reduce the impact of climate change in this world ,planting more trees with reduce natural disaster , recharge groundwater and prevent soil erosion which will reduce the problem of water crisis and food security in the world and in particularly India . Climate change has affected marine life with excess industrial waste and plastic waste being thrown into the river and oceans , million of tonnes of waste is thrown into the rivers which is eaten by the marine life leading to death and ultimate in the name of fish we are consuming plastic these days .